Analisis Hukum Islam Terhadap Tradisi Sumbangan Dalam Walimah Al-’Urs - Aljamilah, Afrohah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2023)
The donation tradition in Walimah al-'urs in Tawangrejo Jatipurno Wonogiri Village is an interest phenomenon, because the process carried out without being organized by a leader of the tradition. In this tradition there is a legal risk that there is a difference in understanding whether the tradition can be applied or not, and whether the transaction is a loan or a gift, which in turn has an impact on the return process. The purpose of this study is to discuss the analysis of Islamic law on donations in walimah al-'urs in Tawangrejo Jatipurno Wonogiri Village. The approach in this study use a qualitative approach to the type of case study research. The research data was collected through observation and interviews. The analysis process uses the theory of 'urf and fiqh hibah and qard . From this research it can be stated that the implementation of the tradition of donations in walimah al-'urs in the village of Tawangrejo Jatipurno Wonogiri has been going on for a long time from generation to generation, the aim is as an effort to help each other and to maintain the honor/esteem of guests invited to walimah al-'urs . Analysis of Islamic law on donations in walimah al-'urs that have been running in Tawangrejo Village is included in the category of bi ats-tsawab grants (grants that expect rewards), because there is the same 'illat between the donation procession that applies in society and grant transactions, namely lies in the non-obligation to return donations. Meanwhile, returning the donation is nothing but part of one's noble character